Planning Approaches To Preservation And Renovation In Nanluogu Xiang Area - Zuo Chuan (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
On the basis of a thorough and detailed investigation into the present condition and communal problems in Nanluogu Xiang area, the City Research Group of the Institute from Architecture and Urban Studies, Tsinghua University, has accomplish some tentative studies and produced some planning policies. This paper attempts to tackle the problems in preservation and renovation of the overall physical environment, in this area. In addition, a further discussion is made on a few common problems, such as the scale and effect of Old City preservation and renovation, redistribution of land value, public participation and support, and protection of interest of residents and the district.Situated in the southeast of Gulou (Drum Tower) of the Old City of Beijing, Nanluogu Xiang neighborhood is surrounded by Di'anmenwai Street, Jiaodaokou South Street, Gulou East Street and Kuanjie Street, covering about 84 hectares' of land. At present, Hutong are well laid out and courtyard houses nicely preserved in the center of this neighborhood, and the entire neighborhood is one of the most important single